Using classroom response systems for creative interaction and engagement with students - Paul Middleditch; Will Moindrot (Cogent Economics & Finance, 2015)
Recent changes to the landscape of higher education and the student environment generally has brought renewed focus on the need for pedagogical innovation. The importance of student satisfaction and the accompanying rising expectations of the technologically savvy generation of students have brought significant challenges to an academic community already busied with the pedagogically sound delivery of undergraduate taught courses. This new environment has inevitably led to a demand for tools that can assist convenors to meet those challenges without overburdening already tight workloads. This paper presents evidence on the innovative use of one such tool in the form of an over web classroom response system, introduced with the aim of meeting the challenges of the new era in higher education. We suggest that the use of this type of technology can increase student satisfaction and enjoyment as a driver for creative engagement.
Keywords: 330; large group classes; higher education; classroom response system; student response system; clickers; peer interaction; economic tools for teaching